(3GdGeGeI h GdSjGSI (B1 :s (3GdLRA GdChd (B/s - (3Hf bJjHI,YHO Gddg Hf eSde s; (3HhRjOI(B,(3YHO GdQMeGfs ([(3Ohf ecGf(B] :s (3ehae ddfTQh GdJhRjY ,s, 1989)
(3GYGOI fTQ cJGH GdGeGeI h GdSjGSI ef TCfg Gf jKQj fXQJfG ddUQGY GdSjGSj h GdePgHj GdPj OGQ GHGf GdYUhQ GdZSdGejI GdChdi GdJj cGfJ CcKQ GROgGQG h YWGA ef ZjQgG QZe cd GdaJf h GdUQGYGJ GdJj OGQJ ajgG ceG Gfg ef TCfg Gf jPcQfG HGdhGbYjI h GdehVhYjI GdJj jJMdi HgG GdbOeG aj MOjKge Yf CLd GdhbGFY GdeJYdbI HebOSGJfG cQhGjI ebJd YKeGf h eG hbY jhe GdMQIh ZjQPdc ef GdhbGFYh gj hGbYjI fMf aj CTO GdMGLI GdjgG Gdjhes
Keywords: (3GdUQGY GdSjGSjs; (3GdYUQ GdESdGejs